IMPROVEMENT PRODUK HAMMOCK SLEEPING BAG DENGAN METODE QFD (QUALITY FUNCTION DEPLOYMENT) - Ahmad Kasan; Antoni Yohanes (Jurnal Ilmiah Dinamika Teknik, 2017)
This research was conducted in order to develop products Hammock Sleeping Bag manufactured by "Hang". Hang is a brand of manufacturers scale home industry located in the area Pusponjolo, Semarang. A wide variety of manufactured products such as hammock, cover bag, backpack, briefcase slempang, cell phone holster, T-shirt screen printing. Quality Function Deployment (QFD) is used to bring what consumers want and what they can do manufacturers to meet consumer desires. This product design development research using questionnaires as a data collection tool. The data obtained from consumers and then processed. After knowing the results if the data from the data collected is then made quality house or House of Quality. After the analysis found that the necessary development of variations of the raw material in order to stimulate the development of product design Hammock, so that consumers have many choices determine the type of product to be purchased. Thus increase the chances of customer satisfaction. Keywords : Quality Function Deployment (QFD), House of Quality (HOQ). Product development